Transplantation of organs from deceased donors with meningitis and encephalitis: a UK registry analysis. Issue 6 (3rd December 2016) - Trotter, Patrick B.; Robb, Matthew; Hulme, William; Summers, Dominic M.; Watson, Christopher J. E.; Bradley, J. Andrew; Neuberger, James
Abstract: Background: Deceased organ donors, where the cause of death is meningitis or encephalitis, are a potential concern because of the risks of transmission of a potentially fatal infection to recipients. Methods: Using the UK Transplant Registry, a retrospective cohort analysis of deceased organ donors in the UK was undertaken to better understand the extent to which organs from deceased donors with meningitis and/or encephalitis (M/E) (of both known and unknown cause) have been used for transplantation, and to determine the associated recipient outcomes. Results: Between 2003 and 2015, 258 deceased donors with M/E were identified and the causative agent was known in 188 (72.9%). These donors provided 899 solid organs for transplantation (455 kidneys and 444 other organs). The only recorded case of disease transmission was from a donor with encephalitis of unknown cause at time of transplantation who transmitted a fatal nematode infection to 2 kidney transplant recipients. A further 3 patients (2 liver and 1 heart recipient) died within 30 days of transplantation from a neurological cause (cerebrovascular accident) with no suggestion of disease transmission. Overall, patient and graft survival in recipients of organs from donors with M/E were similar to those for all other types of deceased organ donor. Conclusion: Donors dying with M/E represent a valuable source of organs for transplantation. The risk of disease transmission is low but, where the causative agent is unknown, caution is required.